Think Pair Share VS Team Pair Solo on Students' Writing Procedure Text - Syuroya Ayu Fitriani; Testiana Deni Wijayatiningsih; Siti Aimah (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
This research aimed to find the significant differences of students' achievement in writing procedure text using team pair solo and think pair share, This research used a quantitative and experimental method. The research design was pretest posttest control group. The population was the students of class VII SMPN 33 Semarang by using simple random sampling was VII D as the experimental group, VII C as the control group, and VII B as the tryout class. The research instruments used were test and questionnaire. The result of the test is t arithmetic is lower than t table so the hypothesis is not accepted. It means that there is no significant difference of students achievement in writing procedure text between students who were taught writing using team pair solo and those who were taught by using think pair share. The result of posttest in experimental class is 77.61 and control class is 77.38.